Fetal cardiology : embryology, genetics, physiology, echocardiographic evaluation, diagnosis, and perinatal management of cardiac diseases - Yagel, Simcha; Silverman, Norman H.; Gembruch, Ulrich; Cohen, Sarah Margalyt (Boca Raton : CRC Press, 2019)
The third edition of this established reference is the product of the combined efforts of many professionals - obstetricians, pediatric cardiologists, sonographers, molecular biologists, and medical physicists - and is a comprehensive guide intended for anyone interested in scanning the fetal cardiac system.
OCLC-licensed vendor bibliographic record.
Keywords: Fetal heart -- Diseases; Fetal heart; MEDICAL -- Gynecology & Obstetrics; MEDICAL -- Pediatrics; MEDICAL -- Perinatology & Neonatology